2022
DOI: 10.3390/nu14194128
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Flavonoids on Animal Models of Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common gynecological endocrinopathies. Evidence suggest that flavonoids have beneficial effects on endocrine and metabolic diseases, including PCOS. However, high-quality clinical trials are lacking. We aimed to conduct a systematic review and meta-analysis of experimental studies to determine the flavonoids’ effects in animal models of PCOS. Three electronic databases including PubMed, Scopus, and Web of Science were systematically searched from their incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Recent research highlights that the effects of natural products depend significantly on their (micro)environment, cell type, and nanoformulation, allowing for the development of various drug delivery systems [ 77 ]. Previous systematic reviews and meta-analyses have identified factors such as the induction agent, type of natural product, route of drug delivery, animal model, treatment dosage, and duration of administration as potential sources of substantial heterogeneity between studies [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research highlights that the effects of natural products depend significantly on their (micro)environment, cell type, and nanoformulation, allowing for the development of various drug delivery systems [ 77 ]. Previous systematic reviews and meta-analyses have identified factors such as the induction agent, type of natural product, route of drug delivery, animal model, treatment dosage, and duration of administration as potential sources of substantial heterogeneity between studies [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marigold leaf extract is believed to contain active compounds that can influence the regulation of reproductive hormones [34]. The elevation of FSH levels after Marigold leaf extract administration can have a stimulating effect on the ovaries [35]. FSH is an important hormone in regulating the growth of ovarian follicles and the secretion of estrogen hormones [36].…”
Section: Effect Of Administration Of Ethanol Extract Of Marigold Leav...mentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS), characterized by chronic anovulation, hyperandrogenism, and insulin resistance, is one of the most common reproductive endocrinopathy affecting approximately 8% to 18% reproductive-aged women [ 1 ]. In addition to being an important cause of infertility, it is also a risk factor for many metabolic diseases, such as type 2 diabetes mellitus, cardiovascular continuum, and endometrial carcinoma [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%